2014
DOI: 10.5370/jeet.2014.9.4.1375
|View full text |Cite
|
Sign up to set email alerts
|

Flashover Prediction of Polymeric Insulators Using PD Signal Time-Frequency Analysis and BPA Neural Network Technique

Abstract: -Flashover of power transmission line insulators is a major threat to the reliable operation of power system. This paper deals with the flashover prediction of polymeric insulators used in power transmission line applications using the novel condition monitoring technique developed by PD signal time-frequency map and neural network technique. Laboratory experiments on polymeric insulators were carried out as per IEC 60507 under AC voltage, at different humidity and contamination levels using NaCl as a contamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…where S k and Y k are respectively the desired and measured output for the k th input set and m is the total number of input sets [15,[22][23]. The details of the optimized neural network used in the present study are shown in Table 2.…”
Section: Real Time Fault Diagnosis Results From Labview-ann Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…where S k and Y k are respectively the desired and measured output for the k th input set and m is the total number of input sets [15,[22][23]. The details of the optimized neural network used in the present study are shown in Table 2.…”
Section: Real Time Fault Diagnosis Results From Labview-ann Approachmentioning
confidence: 99%
“…LabVIEW utilizes graphical programming language developed by National Instruments and it has been successfully applied for data acquisition, instrument control and industrial automation [19][20][21]. Artificial Neural Network (ANN) is a powerful tool in the classification of patterns through learning and nonlinear mapping [22][23]. Deploying both LabVIEW and ANN is considered to be necessary as a further toolset for researchers.…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, PD detection and analysis is a well recognized insulation condition monitoring method in determining the quality of insulation. Since the dry band partial arcs due to wet pollution are a precursor of flashover, the PD measurement and analysis will provide better mechanism to effectively understand the pollution performance of the aged polymeric insulators [16][17][18]. However, the pollution performance of aged polymeric insulators considering the effects of water absorption stress and thermal stress using the advanced PD signal measurement and analysis has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, it is not economical to measure for all time. It is very difficult to install such data acquisition system to many buildings because of high costs and application on power electronics with algorithms [17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%